2023
DOI: 10.3389/fmed.2023.1143485
|View full text |Cite
|
Sign up to set email alerts
|

Serial viral load analysis by DDPCR to evaluate FNC efficacy and safety in the treatment of mild cases of COVID-19

Abstract: IntroductionThe SARS-CoV-2 outbreak has threatened the human population globally as the numbers of reinfection cases even after large-scale vaccination. Trials have been carried out to find drugs effective in fighting the disease, as COVID-19 is being considered a treatable disease only after we have antivirals. A clinical candidate originally developed for HIV treatment, AZVUDINE (FNC), is a promising drug in the treatment of COVID-19.MethodsTo predict the clinical outcome of COVID-19, we examined the course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…5 The Phase III study of Azvudine, which included a total of 143 participants in the Azvudine group, showed that it could shorten the time to negative nucleic acid conversion and reduce viral load in mild to moderate patients. 13 However, these The results of this study showed that Azvudine could reduce overall mortality compared to the control group when using IPTW for data processing. However, when using propensity score matching for data processing, this outcome measure did not…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…5 The Phase III study of Azvudine, which included a total of 143 participants in the Azvudine group, showed that it could shorten the time to negative nucleic acid conversion and reduce viral load in mild to moderate patients. 13 However, these The results of this study showed that Azvudine could reduce overall mortality compared to the control group when using IPTW for data processing. However, when using propensity score matching for data processing, this outcome measure did not…”
Section: Discussionmentioning
confidence: 62%
“…In a single‐arm compassionate use trial ( n = 31), all COVID‐19 patients who received oral Azvudine achieved recovery, with a 100% viral NANC rate in 3.29 ± 2.22 days and a 100% hospital discharge rate in 9.00 ± 4.93 days 5 . The Phase III study of Azvudine, which included a total of 143 participants in the Azvudine group, showed that it could shorten the time to negative nucleic acid conversion and reduce viral load in mild to moderate patients 13 . However, these studies only measured outcomes based on the time to negative nucleic acid conversion or viral load levels, and there was a lack of research on clinically important outcomes, such as disease progression rate and all‐cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…As the rst launched Chinese oral anti-COVID-19 drug [8], Azvudine exhibited antiviral activity effectively against coronavirus in preliminary clinical trials [2,4,9,10,11]. Meanwhile, several retrospective cohort studies suggested that Azvudine showed more effectiveness in hospitalized COVID-19 patients compared with Nirmatrelvir-ritonavir and Paxlovid in terms of composite disease progression outcome [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…In phase III clinical trial (trial number: NCT05033145), mild COVID‐19 patients who received Azvudine treatment experienced a shorter NANC by an average of 2.7 d compared to those in the placebo group. [ 34 ] Compared to placebo groups, Azvudine showed good safety. The adverse reactions included headache, dizziness, AST increase, nausea, ALT increase, and D Dimer increase and were the same as those related to antiviral drugs.…”
Section: Clinical Studiesmentioning
confidence: 99%